PLANETS IN YOUR HAND: The social impact of a tactile experience - Athanasopoulos, Dimitrios; Gazeas, Kosmas; Palafouta, Sofia; Panagopoulou, Maria; Vrontaki, Konstantina; Papadami, Argiro (European Planetary Science Congress, 2020)
Planets In Your Hand is a science education program, that consists of a portable interactive exhibition of eight planetary surface models. The program offers the visitors a tactile experience and the opportunity to understand the diversity of the planetary surfaces in our Solar System. The planetary models have been exhibited in a series of public events since their construction in 2018 and have been visited by a wide range of audience, including visually impaired people. The project is still running, while Planets In Your Hand team is working on improvements, that foresee to a greater social and educational impact. The current work summarizes the social impact of the program through the visitors" questionnaires, comments and impressions.1. IntroductionPlanets In Your Hand (PIYH) is a science communication project, initiated at the Department of Physics of National and Kapodistrian University of Athens (NKUA). Its purpose is to reach individuals, that do not have any previous interaction with the field, trigger their interest to interactively participate in scientific activities and public events and eventually bring them closer to science and contribute in lifelong learning. This is mainly attempted through a visual and tangible representation of the planetary environments and morphologies in our Solar System (Kefala et al., 2018), that also benefits visually impaired people.The success of PIYH project is established by the Science Communication Award (EΠI2 Award 2019) in the category of "Awareness Activities and Campaigns".PIYH program is a non-formal learning experience, the importance of which is widely accepted and supported by the National Science Education Standards (National Research Council, 1996). The way science communication is organized and planned as well as the visitor"s intrinsic motivation for learning (Eshach 2007) declares this an indisputable fact.2. Data CollectionIn order to evaluate the social impact of the PIYH project, questionnaires were filled out by the visitors after their conceivable journey to our Solar System. Multiple-choice questions and a comment section were included. The goal was to examine whether the exhibition provides an overall positive experience to the visitors and to find possible ways to improve its presentation.The planetary models have been exhibited in a series of public events (Fig. 1) since the beginning of the program (Palafouta et al., 2019). This research was conducted during two major events where PIYH was presented. These are the opening of the exhibition and the Athens Science Festival 2019.Oral impressions and evaluations for every event were also made directly by the members of the PIYH team that presented the planetary surfaces. They were based on the reactions and the comments of the visitors and were really helpful. PIYH program is a non-formal learning experience, the importance of which is widely accepted and supported by the National Science Education Standards (National Research Council, 1996). The way science communication is organized and planned as well as the visitor"s intrinsic motivation for learning (Eshach 2007) declares this an indisputable fact.3. The social impactThe questionnaire provided an overall positive feedback by the visitors. As shown in Fig. 2 the majority (97.5 %) of the visitors were pleased with PIYH project and the exhibition. Early ages (≤23 years old) occupy great percentage (61 %) of the visitors, while the rest include individuals, parents or educators.The overwhelming majority of the participants (98.5%) would recommend the exhibition to a friend, enhancing the social impact of the project, while many parents and educators mentioned that this project can trigger new generations to engage with Astrophysics and science in general.More than 47% of the visitors shared their impressions through additional comments. Positive remarks were given, for the exhibition and its presentation by the PIYH team members.Visually impaired people commented positively, mentioning that exhibitions in general do not offer tangible experience, and they are limited to an oral, acoustic or pre-recorded presentation. PIYH exhibition gave them for the first time the sense of planetary scale, surface characteristics and the unique opportunity to interact with planetary surfaces.A wide range of reactions was perceived by the PIYH team members during the events with respect to the visitor"s background in astrophysics.Regardless of their age, people who were getting in touch with Planetary Science for the first time were curious to touch and feel the surface"s differences, asking questions about the internal and external structure and the atmospheric phenomena of each planet. Those who had scientific background, combined facts and knowledge from their own scientific field with the information provided during the events.On the other hand, visitors familiar with astronomy and planetary science expressed more elaborate questions, many of which concerned the current research on space exploration.4. Summary and ConclusionsThis research has shown that people of different age and scientific background can be brought together through an interactive and tangible educational experience. PIYH exhibition is considered a pleasant and memorable experience according to the conducted analysis. The project attracted individuals that have no previous interaction with the field of Planetary Science, triggering their interest and brought together people who are already interested or contribute to science. PIYH project makes this learning experience accessible to visually impaired people, encouraging this way the local community to create similar activities. It is an alternative, creative and interesting way of learning about our Solar System. Similar projects can be inspired by PIYH program and engage the general public in science through a pleasant and cognitively successful way, enhancing the communication of science in many fields.References[1] Eshach, H., 2007, Journal of Science Education and Technology, 16, 171-190.[2] Kefala, K., et al., 2018, EPSC2018,1251-2.[3] National Research Council, 1996.National Science Education Standards. Washington DC: National Academy Press.[4] Palafouta, S., et al., 2019, EPSC-DPS2019, 1816-1